Mechanisms of migrant exclusion: Temporary labour, precarious noncitizenship, and technologies of detention. Issue 5 (17th July 2021) - Parreñas, Rhacel; Landolt, Patricia; Goldring, Luin; Golash‐Boza, Tanya; Silvey, Rachel
Abstract: 'Mechanisms of Migrant Exclusion' focuses on the exclusionary measures that migrant workers confront. Although migration studies have long attended to various social and structural systems of exclusion, for instance, xenophobia and nativism (De Genova, 2005, https://doi.org/10.1515/9780822387091 ; Golash‐Boza, 2011, https://doi.org/10.4324/9780203123928, and 2015, https://doi.org/10.18574/nyu/9781479894666.001.0001 ), recent global shifts in immigration politics and temporary labour regimes have increased the urgency of attending to the rise of global and transnational systems or regimes of exclusion. Internationally, noncitizens have grown increasingly vulnerable to detention and deportation (Mountz, 2020, 10.5749/j.ctv15d8153), whereas migrant contract workers continue to be systematically denied rights and protections in the labour market (Strauss and McGrath, 2017, 10.1016/j.geoforum.2016.01.008). These mechanisms of exclusion illustrate the range of limitations faced by migrants, particularly those who are undocumented, refugees, or temporary workers.